2014
DOI: 10.3892/mmr.2014.3073
|View full text |Cite
|
Sign up to set email alerts
|

Identification of histamine receptor subtypes in skeletal myogenesis

Abstract: To date, conventional and/or novel histamine receptors (HRs) have not been investigated in mouse skeletal myogenesis. Therefore, the present study aimed to investigate the HR-subtypes in skeletal myogenesis. The myogenesis of C2C12 skeletal myoblasts was evaluated using desmin, myogenin and myosin heavy chain (Myh) as early, intermediate and late differentiation markers, respectively. Reverse transcription-quantitative polymerase chain reaction and immunostaining were performed and the messenger RNA (mRNA) exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
(29 reference statements)
2
14
0
Order By: Relevance
“…Morphological changes to C2C12 myoblasts cultured in control-vehicle (Con-Ve), E2, EPA and E2/EPA solutions were determined by immunofluorescence following treatment with anti-Desmin mouse antibody known to be expressed in both myoblasts and myotubes with increased expression as differentiation progresses [27]. When using immunofluorescent analyses, the staining is weak in the cytoplasm of undifferentiated myoblasts and gradually intensifies in elongated myocytes, early tubes and myotubes.…”
Section: Morphological Changes and Myoblast Fusion Indexmentioning
confidence: 99%
“…Morphological changes to C2C12 myoblasts cultured in control-vehicle (Con-Ve), E2, EPA and E2/EPA solutions were determined by immunofluorescence following treatment with anti-Desmin mouse antibody known to be expressed in both myoblasts and myotubes with increased expression as differentiation progresses [27]. When using immunofluorescent analyses, the staining is weak in the cytoplasm of undifferentiated myoblasts and gradually intensifies in elongated myocytes, early tubes and myotubes.…”
Section: Morphological Changes and Myoblast Fusion Indexmentioning
confidence: 99%
“…The lowest (R)-α-MeHA concentration used (1 nM) was below the agonist affinity for H 3 receptor (pK i ¼ 8.4) in the brain (Chen et al, 2003 andLi et al, 2014) and had no effect on the cytoplasmic Ca 2 þ imaging under electrical stimulation in our study. On the other hand, the highest (R)-α-MeHA concentration used (100 μM) was also less active, probably because of combinatorial effects, due to nonspecific activation of other receptors (H 1 receptor or H 2 receptor) on the cell membrane (Chen et al, 2015), which counteracted the response (Leurs et al, 1998), or probably as a self-protective mechanism. The highest inhibitory effect of 1 μM (R)-α-MeHA, exerted after 10-min or 20 min treatment, was in agreement with a previous pharmacological study on histamine receptor ligands, where (R)-α-MeHA also showed the highest efficacy at 1 μM (Kottke et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…21 In the early-phase of myoblast differentiation in vitro, high levels of histamine receptor expression can be detected, suggesting that histamine may participate in myoblast proliferation. 22 A previous study also reported that histamine could stimulate the expression of IGF-1 in human glioma cells. 23 These studies suggest that histamine may have an impact on the proliferation and differentiation of myoblasts and muscle regeneration.…”
mentioning
confidence: 91%
“…A recent study found that histamine therapy reduces muscle injury and improves grip strength of Dmd mdx mice, but its underlying mechanism has not been reported . In the early‐phase of myoblast differentiation in vitro, high levels of histamine receptor expression can be detected, suggesting that histamine may participate in myoblast proliferation . A previous study also reported that histamine could stimulate the expression of IGF‐1 in human glioma cells .…”
Section: Introductionmentioning
confidence: 97%